Medieval Islamic sectarianism - Baker, Christine D. (Past imperfect (ARC Humanities Press), 2019)
This book asks readers to re-examine their view of the Islamic world and the development of sectarianism in the Middle East by shining a light on the complexity and diversity of early Islamic society. While Sunni Islam eventually became politically and numerically dominant, Sunni and Shiʻi identities took centuries to develop as independent communities. When modern discussions of sectarianism in the Middle East reduce these identities to a 1400-year war between Sunnis and Shiʻis, we create a false narrative